2022
DOI: 10.3389/fimmu.2022.837767
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk Between Natural Killer T and Dendritic Cells and Its Impact on T Cell Responses in Infections

Abstract: Both innate and adaptive immunity is vital for host defense against infections. Dendritic cells (DCs) are critical for initiating and modulating adaptive immunity, especially for T-cell responses. Natural killer T (NKT) cells are a small population of innate-like T cells distributed in multiple organs. Many studies have suggested that the cross-talk between these two immune cells is critical for immunobiology and host defense mechanisms. Not only can DCs influence the activation/function of NKT cells, but NKT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…A large number of DAMPs can activate the innate immune system by binding to PRRs on the surface of a variety of immune cells, mediating downstream inflammatory pathways to generate a range of cytokines and chemokines. As a conserved T cell subline, NKT cells can be activated and then rapidly produce cytokines in response to antigen presentation by DCs 19 , 20 , while CXCL6-expressing DCs can bind to NKTs expressing the chemokine receptor CXCR6 to promote NKT cell activation/maturation 21 . Activated NKT cells promote CD4 + T cell differentiation and act on Kupffer cells by further generating IL-17, inducing downstream pro-inflammatory mediator expression 22 25 , and generating large amounts of ROS, which can further act on HSEC and hepatocytes to promote programmed cellular death or necrosis, expanding the inflammatory cascade 26 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of DAMPs can activate the innate immune system by binding to PRRs on the surface of a variety of immune cells, mediating downstream inflammatory pathways to generate a range of cytokines and chemokines. As a conserved T cell subline, NKT cells can be activated and then rapidly produce cytokines in response to antigen presentation by DCs 19 , 20 , while CXCL6-expressing DCs can bind to NKTs expressing the chemokine receptor CXCR6 to promote NKT cell activation/maturation 21 . Activated NKT cells promote CD4 + T cell differentiation and act on Kupffer cells by further generating IL-17, inducing downstream pro-inflammatory mediator expression 22 25 , and generating large amounts of ROS, which can further act on HSEC and hepatocytes to promote programmed cellular death or necrosis, expanding the inflammatory cascade 26 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis not only demonstrated an increased percentage of dendritic cells but, importantly, a reduced proportion of immunosuppressive iNOS-producing dendritic cells within the tumor environment of metformin-treated mice ( Figure 5 I,J). These findings imply that metformin’s modulatory effects on the immune system may involve intricate interactions between NKT cells and dendritic cells, thus potentially altering T cell phenotypes to bolster anticancer immunity [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells (DCs) are an important cell type in the immune system, responsible for antigen presentation and promoting immune responses by activating specific T cells (15). Dendritic cells possess highly differentiated cell surface molecules, including HLA-DR, CD86, and CD54, which play important roles in the process of dendritic cell activation of T cells (21)(22)(23)(24)(25). This study found that patients with ACLF exhibited significantly reduced expression of surface markers HLA-DR, CD86, and CD54 compared to patients with CHB or healthy individuals.…”
Section: Discussionmentioning
confidence: 99%